Bentuk Representasi Diri Fashion Stylist Pada Media Sosial Instagram - Janna Panayanti; Hendri Prasetyo; Yunita Sari; Yubali Ani (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
The aim of this research is to present a form of self-representation of a fashion stylist through the social media Instagram. This research uses a qualitative approach with phenomenological methods. Data collection was carried out by observing the four fashion stylists on Instagram social media. The research results show: The form of self-representation of a fashion stylist on Instagram social media must pay attention to: 1) The strategies used in self-presentation, namely Ingratiation and Self-Promotion; 2) The form of the upload that is uploaded displays the impression as expected; 3) Fashion stylists also control every upload they make on their social media, especially those related to their profession as a fashion stylist, and 4) Efforts to build their own identity.